COMPARISON OF ANTIBACTERIAL EFFECTIVENESS OF STEVIA REBAUDIANA ON streptococcus mutans AND streptococcus sanguinis - Massón- Palacios, Maria (2016)
Objectives: To compare the efficiency of the natural sweetener Stevia prepared as aqueous extract, both industrial and commercialformulas, on the growth of mutans streptococci and streptococcus sanguis. Materials and methods: 15 Petri dishes were preparedwith Mueller Hinton agar supplemented with 5% of sheep blood, for each studied microorganism, streptococcus sanguis ATCC 10556and mutans streptococci ATCC 25175, the previously activated strains were planted and cultivated for 48 hours, felt disks soaked ineach of stevia formulas were positioned on each petri dish. Results: Industrial Stevia formula was the most effective, according to theKruskal-Wallis test, showing better performance with 107% variation in relation to the aqueous extract on mutans streptococci formula,and 56% on streptococcus sanguis. Conclusions: Stevia on industrial formula is suitable for use in substances and/or foods, howeverfuture studies must be performed seeking to